A Phase Ib/II Study of the JAK1 Inhibitor, Itacitinib, plus nab‐Paclitaxel and Gemcitabine in Advanced Solid Tumors. (16th August 2018) - Beatty, Gregory L.; Shahda, Safi; Beck, Thaddeus; Uppal, Nikhil; Cohen, Steven J.; Donehower, Ross; Gabayan, Afshin Eli; Assad, Albert; Switzky, Julie; Zhen, Huiling; Von Hoff, Daniel D.
Abstract: Lessons Learned: Itacitinib in combination with nab ‐paclitaxel plus gemcitabine demonstrated an acceptable safety profile with clinical activity in patients with advanced solid tumors including pancreatic cancer. The results support future studies of itacitinib as a component of combination regimens with other immunologic and targeted small molecule anticancer agents. Background: Cytokine‐mediated signaling via JAK/STAT is central to tumor growth, survival, and systemic inflammation, which is associated with cancer cachexia, particularly in pancreatic cancer. Because of their centrality in the pathogenesis of cancer cachexia and progression, JAK isozymes have emerged as promising therapeutic targets. Preclinical studies have demonstrated antiproliferative effects of JAK/STAT pathway inhibition in both in vitro and in vivo models of cancer, including pancreatic cancer. Methods: This phase Ib/II dose‐optimization study assessed itacitinib, a selective JAK1 inhibitor, combined with nab ‐paclitaxel plus gemcitabine in adults with treatment‐naïve advanced/metastatic disease (Part 1) or pancreatic adenocarcinoma (Parts 2/2A; NCT01858883). Starting doses (Part 1) were itacitinib 400 mg, nab ‐paclitaxel 125 mg/m 2, and gemcitabine 1, 000 mg/m 2 . Additional dose levels incorporated were granulocyte colony‐stimulating factor, de‐escalations of itacitinib to 300 mg once daily (QD), nab ‐paclitaxel to 100 mg/m 2, and gemcitabine to 750 mg/m 2 . Results: Among 55 patients in Part 1, 6 developed seven hematologic dose‐limiting toxicities (Cycle 1). Itacitinib 300 mg plus nab ‐paclitaxel 125 mg/m 2 and gemcitabine 1, 000 mg/m 2 was tolerated and expanded in Part 2. Treatment discontinuation and grade 3/4 neutropenia rates prompted itacitinib de‐escalation to 200 mg QD in Part 2A. The most common grade 3/4 toxicities were fatigue and neutropenia. Partial responses occurred across all itacitinib doses and several tumor types (overall response rate, 24%). Conclusion: Itacitinib plus chemotherapy demonstrated acceptable safety and clinical activity in patients with advanced solid tumors including pancreatic cancers. This study was terminated early (sponsor's decision) based on negative phase III results for a JAK1/2 inhibitor in previously treated advanced pancreatic cancer.